2013
DOI: 10.1016/j.healun.2013.01.906
|View full text |Cite
|
Sign up to set email alerts
|

Lung Size Mismatch and Primary Graft Dysfunction after Bilateral Lung Transplantation

Abstract: BACKGROUND-Donor to recipient lung size matching at lung transplantation (LTx) can be estimated by the predicted total lung capacity (pTLC)ratio (donor pTLC/recipient pTLC). We aimed to determine whether the pTLC-ratio is associated with the risk of primary graft dysfunction (PGD) after bilateral LTx (BLT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…Female donors tend to be smaller in size than male donors; this size discrepancy can contribute to PGD. 10,11,19 Conversely, female recipients can do well no matter what size graft they receive; their slightly lower metabolic demand accommodates smaller grafts, and larger grafts can reduce PGD. 11 There may also be a selection bias for females who survive to transplant.…”
Section: Gender Effects On Bronchiolitis Obliteransfree Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Female donors tend to be smaller in size than male donors; this size discrepancy can contribute to PGD. 10,11,19 Conversely, female recipients can do well no matter what size graft they receive; their slightly lower metabolic demand accommodates smaller grafts, and larger grafts can reduce PGD. 11 There may also be a selection bias for females who survive to transplant.…”
Section: Gender Effects On Bronchiolitis Obliteransfree Survivalmentioning
confidence: 99%
“…10,11,19 Conversely, female recipients can do well no matter what size graft they receive; their slightly lower metabolic demand accommodates smaller grafts, and larger grafts can reduce PGD. 11 There may also be a selection bias for females who survive to transplant. Sell and colleagues demonstrated that patients (often females) with shorter stature have a 62% higher death or removal rate on the waitlist due to clinical deterioration.…”
Section: Gender Effects On Bronchiolitis Obliteransfree Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Характер влияния данного несоответствия на вероятность развития осложнений, в частности ПДЛТ, зависит от основного заболевания и того, как оно изменяет объем плевральных полостей и механику дыхания [65].…”
Section: осложнения ассоциированные с несоответствием размеров трансunclassified
“…Indeed, there are some data that would suggest that oversized allografts are associated with a decreased risk of higher-grade primary graft dysfunction. 6 One explanation for this finding is that an oversized allograft may receive a more protective ventilatory strategy (inherent to the smaller tidal volume ratio) and operate at lower pulmonary vascular resistance relative to the amount of blood flow for that lung. Although some progress is being made, we have surprisingly limited published data on this topic to guide surgeons in the decision-making for size matching of donors and recipients.…”
mentioning
confidence: 99%